2017
DOI: 10.1155/2017/7304643
|View full text |Cite
|
Sign up to set email alerts
|

(Mesenchymal) Stem Cell-Based Therapy in Cisplatin-Induced Acute Kidney Injury Animal Model: Risk of Immunogenicity and Tumorigenicity

Abstract: Pathogenesis of AKI is complex and involves both local events in the kidney as well as systemic effects in the body that are interconnected and interdependent. Despite intensive investigations there is still no pharmacological agent that could provide complete protection against cisplatin nephrotoxicity. In the last decade mesenchymal stem cells (MSCs) have been proposed as a potentially useful therapeutic strategy in various diseases, including acute kidney injury. Although MSCs have potent immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…In spite of the trophic effects of MSC-EVs in the point of immunomodulation, MSC-EVs treatment potentially mediates negative immunomodulatory effects [113]. For example, Kilpinen et al analyzed the secretomes of umbilical-cord-derived MSC-EVs with or without the interferon-gamma (IFN-γ) stimulus and indicated that EVs from MSCs treated with IFN-γ for 24 h contained major histocompatibility Class I (MHCI) and both α and β units of the proteasome complex required for the antigen presentation and activation of T cells [114].…”
Section: Immunomodulatory Effect Of Evs From Mscs Against Renal Injurymentioning
confidence: 99%
“…In spite of the trophic effects of MSC-EVs in the point of immunomodulation, MSC-EVs treatment potentially mediates negative immunomodulatory effects [113]. For example, Kilpinen et al analyzed the secretomes of umbilical-cord-derived MSC-EVs with or without the interferon-gamma (IFN-γ) stimulus and indicated that EVs from MSCs treated with IFN-γ for 24 h contained major histocompatibility Class I (MHCI) and both α and β units of the proteasome complex required for the antigen presentation and activation of T cells [114].…”
Section: Immunomodulatory Effect Of Evs From Mscs Against Renal Injurymentioning
confidence: 99%
“…To help understand complex mechanisms involved in the development of kidney injury cisplatin rodent model has been developed and extensively used to investigate cisplatin metabolism and the molecular mechanisms of cisplatin nephrotoxicity [ 3 , 4 ] and to test new generations of platinum-based chemotherapy drugs or adjunctive therapies [ 5 , 6 ] or other potential agents [ 7 ] or strategies to prevent or treat AKI (for instance, stem cells) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult and fetal bone marrow-derived mesenchymal stem cells (BM-MSCs) have been shown to be capable of repairing renal function deficits [ 19 , 20 ]. BM-MSCs have potent immunosuppressive properties and their potential application in acute kidney injury animal models has been studied recently [ 21 ]. However, the use of adult BM-MSCs has some limitations such as the low number of MSCs in adult bone marrow, expression of ageing-associated factors, slow expansion rate, early senescence, inactive telomerase, shorter telomeres and restricted differentiation potential [ 22 ].…”
Section: Introductionmentioning
confidence: 99%